Impact of substrate temperature of yttrium doped NiAl bond coat fabricated by using EBPVD on inconel 625. (January 2021) - Kandi, Hemalatha; Koona, Ramji; Raju, G.M.J.
Abstract: The bond coat has been developed on Inconel 625 substrate by using Electron Beam Physical Vapour deposition (EBPVD) method at different substrate temperatures (ie. 873 K and 973 K). Intended for this persistence, the composition of Ni-49.8Al-0.2Y bond coat pellet was prepared. Structural information, Roughness, Morphology of coating have been characterized by using X-Ray Diffraction (XRD), Atomic Force Microscopy (AFM), and Field Emission Scanning Electron Microscopy (FESEM) respectively. Finally, the Coefficient of Thermal Expansion (CTE) is measured by using Dilatometer. Observed that the crystallinity was increased from 29.43 nm to 37.33 nm with increasing the substrate temperature. Also verified peak expansion is decreasing due to increase in substrate temperature. The average roughness increases to 17%. Columnar structure is observed at higher substrate temperature (973 K) of bond coat surface. The CTE of 973 K substrate temperature coating has 1.27 × 10 −5 K −1 at 1000 °C which is increases 8% with the substrate (1.16 × 10 −5 K −1 at 1000 °C). This is accomplished due to addition of Yttrium to bond coat material. These coatings used in thermal barrier applications such as in gas turbines, jet engines, and power aircraft etc. Highlights: Yttrium doped NiAl bond coat is deposited by EB PVD method on Inconel 625 substrate with different substrate temperatures. Phase analysis, Average surface roughness and Surface morphology is measured by XRD, AFM and FESEM. The thermal expansion coefficient is increased to 8% higher than the Inconel 625 substrate to bond coating (973 K).